2021
DOI: 10.1364/ol.435242
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced in situ active tuning of the LSPR of gold nanorods over 90  nm

Abstract: We demonstrate an easy and controllable method for light-induced active tuning of the longitudinal surface plasmon resonance (LSPR) of gold nanorods (AuNRs) over ∼ 94 n m . The red-shift of the LSPR can be controlled by varying the time of exposure to a 532 nm laser. The tuning is achieved by photo-induced dissolution of individual AuNRs by sodium dodecyl sulfate (SDS) under continuous illumination. The dissolution of the AuNRs increases the aspect ratio, and conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…While a redshift in the absence of plasmon excitation is consistent with our previous work as well as studies by others, 37,48,51,52 some reports found blueshifts in the absence of plasmon excitation, assigned to potentially lower ligand coverage at the tips. 35,41,53−55 Here, we immobilized nanorods on a substrate, and plasma cleaned them before dissolution experiments were performed.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…While a redshift in the absence of plasmon excitation is consistent with our previous work as well as studies by others, 37,48,51,52 some reports found blueshifts in the absence of plasmon excitation, assigned to potentially lower ligand coverage at the tips. 35,41,53−55 Here, we immobilized nanorods on a substrate, and plasma cleaned them before dissolution experiments were performed.…”
supporting
confidence: 93%
“…While a redshift in the absence of plasmon excitation is consistent with our previous work as well as studies by others, ,,, some reports found blueshifts in the absence of plasmon excitation, assigned to potentially lower ligand coverage at the tips. ,, Here, we immobilized nanorods on a substrate, and plasma cleaned them before dissolution experiments were performed. Studies in which nanoparticles were also plasma or ozone cleaned all reported redshifts too, while studies that reported blueshifts did not attempt to remove the ligands (see summary in Table S1).…”
supporting
confidence: 91%
See 1 more Smart Citation
“…The optical properties of gold nanoparticles are well known. [ 33 , 34 , 35 ] In order to investigate these properties, the as‐prepared nanoparticles were studied by UV‐Vis absorption spectroscopy (Figure 1 c). The gold nanoparticles show maximum absorption at 524 nm assigned as the localized surface plasmon resonance (LSPR).…”
Section: Resultsmentioning
confidence: 99%
“…The optical properties of gold nanoparticles are well known [33–35] . In order to investigate these properties, the as‐prepared nanoparticles were studied by UV‐Vis absorption spectroscopy (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%